Smartfit Kids: Aplikasi Edukasi Kebugaran JasmaniBerbasis Kearifan Lokal Melalui PermainanTradisional Karo untuk Siswa Sekolah Dasar - Tri Widia Astuti Tamba; Deasyi Natalia Sitepu; Hasiholanta S Sinurat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
ABSTRACT This study aims to develop the SmartFit Kids application as a physical fitness education medium that integrates traditional Karo games for elementary school students. With the increasing use of digital technology and decreasing children's interest in physical activity, innovations that combine technology with local wisdom are needed. This application was designed using the Research and Development (R&D) method with a user-centered design approach on 24 fourth-grade students from SD Swasta Masehi 1 Kabanjahe, Karo Regency. The validation results by media experts obtained a percentage of 82% with a feasible category, while the validation results by material experts also showed a percentage of 82% with a feasible category. Furthermore, product trials on research subjects obtained a percentage of 80%, so that overall this website application was declared suitable for use as a physical education learning medium based on traditional games. Conclusion, this application successfully preserves local Karo culture while meeting the needs of modern physical education with measurable effectiveness. Keywords: Applications, Education, Physical Fitness, Smartfit Kids